Random genome reduction coupled with polyhydroxybutyrate biosynthesis to facilitate its accumulation in Escherichia coli - Ma, Shuai; Su, Tianyuan; Liu, Jinming; Wang, Qian; Liang, Quanfeng; Lu, Xuemei; Qi, Qingsheng (Frontiers in Bioengineering and Biotechnology, 2022)
Genome reduction has been emerged as a powerful tool to construct ideal chassis for synthetic biology. Random genome reduction couple genomic deletion with growth and has the potential to construct optimum genome for a given environment. Recently, we developed a transposon-mediated random deletion (TMRD) method that allows the random and continuous reduction of Escherichia coli genome. Here, to prove its ability in constructing optimal cell factories, we coupled polyhydroxybutyrate (PHB) accumulation with random genome reduction and proceeded to reduce the E. coli genome. Five mutants showed high biomass and PHB yields were selected from 18 candidates after ten rounds of genome reduction. And eight or nine genomic fragments (totally 230.1–270.0 Kb) were deleted in their genomes, encompassing 4.95–5.82% of the parental MG1655 genome. Most mutants displayed better growth, glucose utilization, protein expression, and significant increase of electroporation efficiency compared with MG1655. The PHB content and concentration enhanced up to 13.3–37.2% and 60.2–102.9% when batch fermentation was performed in M9-glucose medium using the five mutants. Particularly, in mutant H16, lacking 5.28% of its genome, the increase of biomass and PHB concentration were more than 50% and 100% compared with MG1655, respectively. This work expands the strategy for creating streamlined chassis to improve the production of high value-added products.